KEBIJAKAN MONETER DALAM MENGATASI INFLASI DI INDONESIA - Farah Fauziyah (Signifikan: Jurnal Ilmu Ekonomi, 2015)
This study aimed to analyze the transmission mechanism of monetary policy in   control the inflation in Indonesia, both in terms of sharia and conventional. The analytical  tools that used  in this research  is  the Autoregessive  Vector (VAR). This VAR research results conducted by Test Impulse Response Function (IRF)  and  the  Test  of  Forecast  Error  Variance  Decomposition  (FEVD).  IRF showed  that the yield on the conventional side (Model I) is variable SBI had a negative impact and bonds provide a positive impact on inflation, while on the sharia (Model II) have a positive impact in terms of reducing inflation. Fluctuation on Islamic monetary transmission mechanism more stable than the conventional monetary policy transmission mechanism. FEVD the model I give a negative contribution in raising inflation about 43.86%, while the second model of a positive contribution in the sense of lowering inflation about to 25.77%. Therefore we can conclude sharia monetary policy transmission mechanism is better than conventional transmission mechanism of monetary policyDOI: 10.15408/sjie.v4i1.2295